Synthesis and control of UPFC system using PI-D and (NEWELM and NIMC) based adaptive control for compensation power in transmission line - Abdelkrim, Bouanane; Merzoug, Yahiaoui; Khaled, Benyahia; Abdelkader, Chaker (International Journal of Engineering and Technology, 2018)
Flexible Alternating Current Transmission System devices (FACTS) are power electronic components. Their fast response offers potential benefits for power system stability enhancement and allows utilities to operate their transmission systems even closer to their physical limitations, more efficiently, with improved reliability, greater stability and security than traditional mechanical switching technology. The unified Power Flow Controller (UPFC) is the most comprehensive multivariable device among the FACTS controllers. According to high importance of power flow control in transmission lines, new controllers are designed based on the Elman Recurrent Neural Network (NEWELM) and Neural Inverse Model Control (NIMC) with adaptive control. The Main purpose of this paper is to design a controller which enables a power system to track reference signals precisely and to be robust in the presence of uncertainty of system parameters and disturbances. The performances of the proposed controllers (NEWELM and NIMC) are based neural adaptive control and simulated on a two-bus test system and compared with a conventional PI controller with decoupling (PI-D). The studies are performed based on well-known software package MATLAB/Simulink tool box.Â Â Â
Keywords: FACTS; UPFC; PI-D; NEWELM; NIMC; Neural Adaptive Control; Synthesis; Stability; Robustness.